QTL Mapping in Three Connected Populations Reveals a Set of Consensus Genomic Regions for Low Temperature Germination Ability in Zea mays L. - Li, Xuhui; Wang, Guihua; Fu, Junjie; Li, Li; Jia, Guangyao; Ren, Lisha; Lubberstedt, Thomas; Wang, Guoying; Wang, Jianhua; Gu, Riliang (Frontiers in Plant Science, 2018)
Improving seed vigor in response to cold stress is an important breeding objective in maize that allows early sowing. Using two cold tolerant inbred lines 220 and P9-10 and two susceptible lines Y1518 and PH4CV, three connected F2:3 populations were generated for detecting QTL related to seed low-temperature germination ability. At 10°C， two germination traits (emergence rate and germination index) were collected from a sand bed and three seedling traits (seedling root length, shoot length and total length) were extracted from paper rolls. Significant correlations were found among all traits in all populations. Via single-population analysis, forty-three QTL were detected with explained phenotypic variance of 0.62%~39.44%. Seventeen QTL explained more than 10 % phenotypic variance; of them sixteen (94.12%) inherited favorable alleles from the tolerant lines. After constructing a consensus map, three meta-QTL (mQTL) were identified to include at least two initial QTL from different populations. mQTL1-1 included seven initial QTL for both germination and seedling traits; with three explaining more than 30% phenotypic variance. mQTL2-1 and mQTL9-1 covered 2-3 initial QTL. The favorable alleles of the QTL within these three mQTL regions were all inherited from the tolerant line 220 and P9-10. These results provided a basis for cloning of genes underlying the mQTL regions to uncover the molecular mechanisms of maize cold tolerance during germination.